Association of Holter-based measures including T-wave alternans with risk of sudden cardiac death in the community-dwelling elderly: the Cardiovascular Health Study. - Stein, Phyllis K; Sanghavi, Devang; Sotoodehnia, Nona; Siscovick, David S; Gottdiener, John (J Electrocardiol, 2010)
BACKGROUND: Sudden cardiac death (SCD) can be the first manifestation of cardiovascular disease. Development of screening methods for higher/lower risk is critical. METHODS: The Cardiovascular Health Study is a population-based study of risk factors for coronary heart disease and stroke those 65 years or older. Forty-nine (of 1649) with usable Holters and in normal sinus rhythm had SCD during follow-up and were matched with 2 controls, alive at the time of death of the case and not experiencing SCD on follow-up. Univariate and multivariate conditional logistic regression determined the association of Holter-based information and SCD. RESULTS: In univariate models, the upper half of ventricular premature contraction (VPC) counts, abnormal heart rate turbulence, decreased normalized low-frequency power, increased T-wave alternans (TWA), and decreased the short-term fractal scaling exponent (DFA(1)) were associated with SCD, but time domain heart rate variability was not. In multivariate models, the upper half of VPC counts (odds ratio [OR], 6.6) and having TWA of 37 muV or greater on channel 2 (OR, 4.8) were independently associated with SCD. Also, the upper half of VPC counts (OR, 6.9) and having a DFA(1) of less than 1.05 (OR, 5.0) were independently associated with SCD. When additive effects were explored, having both higher VPCs and higher TWA was associated with an OR of 8.2 for SCD compared with 2.6 for having either. Also, having both higher VPCs and lower DFA(1) was associated with an OR of 9.6 for SCD compared with 3.1 for having either. CONCLUSIONS: Results support a potential role for 24-hour Holter recordings to identify older adults at increased or lower risk of SCD.
Keywords: Comorbidity; Coronary Artery Disease; Death, Sudden, Cardiac; Electrocardiography, Ambulatory; Female; Humans; Male; Prevalence; Prognosis; Reproducibility of Results; Risk Assessment; Risk Factors; Sensitivity and Specificity; Survival Analysis; Survival Rate; United States; Ventricular Premature Complexes